2014
DOI: 10.1063/1.4904058
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical response of red blood cells entering a constriction

Abstract: Most work on the dynamic response of red blood cells (RBCs) to hydrodynamic stress has focused on linear velocity profiles. Relatively little experimental work has examined how individual RBCs respond to pressure driven flow in more complex geometries, such as the flow at the entrance of a capillary. Here, we establish the mechanical behaviors of healthy RBCs undergoing a sudden increase in shear stress at the entrance of a narrow constriction. We pumped RBCs through a constriction in a microfluidic device and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
1
26
1
Order By: Relevance
“…However, our observations that cells only stretch near the stagnation point indicates that any shear velocity gradient effects due to the top and bottom walls contribute negligibly to cell deformation. This stands in contrast to the study described earlier in which four modes of deformation were observed (23), which featured significant, nonzero shear components in straight, narrow regions of the channel downstream of the extension-dominant converging section.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, our observations that cells only stretch near the stagnation point indicates that any shear velocity gradient effects due to the top and bottom walls contribute negligibly to cell deformation. This stands in contrast to the study described earlier in which four modes of deformation were observed (23), which featured significant, nonzero shear components in straight, narrow regions of the channel downstream of the extension-dominant converging section.…”
Section: Discussioncontrasting
confidence: 99%
“…In a channel converging linearly from large (100 mm wide) to small (20 mm wide) widths over a downstream distance of 70 mm (height a constant 40 mm), four modes of deformation, stretching, twisting, tumbling, and rolling, were observed for cells at different cross-stream positions (23). The stretching mode occurred for red blood cells on the channel centerline where the velocity gradient was symmetric about the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the constriction channel design was used to quantify the mechanical properties of RBCs [23,[27][28][29][30][31][32][33][34][35][36][37][38][39][40]. In 2003, Chiu et al, characterized complex behaviors of Plasmodium falciparum infected RBCs using the constriction channels with sizes at 8, 6, 4, and 2 µm in width [23] (see Figure 1a).…”
Section: Constriction Channel Based Mechanical Property Characterizatmentioning
confidence: 99%
“…[47] Meanwhile, the microfluidic constriction channel is used to quantify the cellular entry and transition process through a micro channel with a cross-sectional area smaller than the dimensions of a single cell, enabling high-throughput single-cell mechanical property characterization [23][24][25][26] (see Table 1). This technique was first used to evaluate the mechanical properties of RBCs [23,[27][28][29][30][31][32][33][34][35][36][37][38][39][40], which was then expanded to study the deformability of WBCs [24,41,42] and tumor cells [25,[43][44][45]. Leveraging mechanical modeling of the cellular entry process into the constriction channel, the microfluidic constriction channel design can collect size-independent intrinsic biomechanical markers such as cortical tension or Young's modulus [35,[46][47][48].…”
Section: Introductionmentioning
confidence: 99%